Student Support, Beyond Empty Signifiers: Insights and Challenges from Enabling Educators - Ana Larsen; Trixie James; Gemma Mann; Kieran Balloo; Susan Hopkins; Marguerite Westacott; Juliette Subraminiam (Student Success)
Student support is a key focus within the widening participation agenda, as effective support enhances retention and success. However, student support is not well defined in higher education, which is problematic as it is difficult to measure success if stakeholders have different definitions. Without clear boundaries in student support, educators who work with marginalised students are at risk of “over-supporting” students or possibly emulating a counselling role. This practice report utilises autoethnography to draw on the lived experience of seven educators working in Enabling programs across four universities. It explores how student support was defined and enacted in their programs and what factors or resources can facilitate or frustrate efforts to effectively support students. The findings highlight the complexity of supporting the multifaceted needs of marginalised students with more nuanced and tailored approaches. The educators in this study collectively emphasised the need for a consistent definition of student support, alongside clear workload allocation and additional training to effectively support students and increase retention and success.